Application of Firefly Optimization Algorithm to the Design and Characterization of Helmholtz Coils for Magnetic Field Sensor Calibration - Sadiq, U. A.; Oluyombo, O. W.; Onuh, S. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper presents the application of Firefly Optimization Algorithm (FOA) to the design and characterization of Helmholtz coils to create homogenous magnetic field needed for calibrating magnetic field sensors and used for other experiments. Magnetometer is used to monitor and record the earth’s magnetic field data at the geomagnetic observatory. Earth’s magnetic field data from ground-based magnetometer observatories are important for studying geomagnetic storm. The absence of earth’s magnetic field data observatories results in a complex mysterious phenomenon of geomagnetic storm and remains as unexplained one. Fluxgate magnetometer is contributing to the ongoing extensive research work dedicated to the explanation of some of the complex phenomena related to geomagnetic storm and solar terrestrial system. In order to examine magnetic field sensing of a fluxgate sensor, a large area with uniform magnetic field is required. The advantage of having a large area is to allow easy access of the sensor during magnetic field measurements. A laboratory design and characterization of high quality Helmholtz coils is a better choice when Helmholtz coil with larger areas that are available in the market are very expensive